2020
DOI: 10.1097/aln.0000000000003127
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Synthase in Peripheral Sensory Neurons Contributes to Mechanical Hypersensitivity during Local Inflammation in Rats

Abstract: Background: Recent emerging evidence suggests that extra-adrenal synthesis of aldosterone occurs (e.g., within the failing heart and in certain brain areas). In this study, the authors investigated evidence for a local endogenous aldosterone production through its key processing enzyme aldosterone synthase within peripheral nociceptive neurons. Methods: In male Wistar rats (n = 5 to 8 per group) with Freund's complete adjuvant hind paw inflammation, the authors examined aldosterone, aldosterone synthase, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…For the first time, we have systematically investigated the potential long-lasting genomic effects of endogenous MR agonist aldosterone on the transcriptional regulation of several pain signaling molecules in peripheral sensory DRG neurons during inflammatory pain. Previous studies have demonstrated MR and its endogenous ligand aldosterone in these neurons [8,9]. Here, chronic i.t.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…For the first time, we have systematically investigated the potential long-lasting genomic effects of endogenous MR agonist aldosterone on the transcriptional regulation of several pain signaling molecules in peripheral sensory DRG neurons during inflammatory pain. Previous studies have demonstrated MR and its endogenous ligand aldosterone in these neurons [8,9]. Here, chronic i.t.…”
Section: Discussionmentioning
confidence: 70%
“…Previously, we have demonstrated that the final conversion of 18-hydroxycorticosterone into aldosterone by aldosterone synthase also occurs in peripheral sensory DRG neurons [9] confirming preceding reports on the expression of aldosterone synthase outside the adrenal gland, e.g., in brain, heart, aortic endothelial cells, and in vascular smooth muscle [24][25][26]. Moreover, we have shown that a single systemic or intrathecal administration of the MR antagonist canrenoate-K resulted in an immediate and short-lasting (up to 30 min) reversal of mechanical hypersensitivity most likely through a nongenomic effect [9]. In contrast to this short-lasting effect, we investigated in this study whether chronic antagonism of aldosterone's action or continuous inhibition of aldosterone synthesis (over 4 days) resulted in alterations of the genomic expression of specific pain signaling molecules such as TRPV1, CGRP, Nav1.8, and trkA and First, we demonstrated that chronic i.t.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spinal cord from adult rats were solubilized and extracted for immunoblotting investigations as previously described [24]. Brie y, the samples were homogenized in boiling SDS sample buffer (100 mM Tris, 2% SDS, 20% glycerol).…”
Section: Western Blotmentioning
confidence: 99%